It Is Impossible That There Could Have Been Nothing: New Support for Cosmological Arguments for the Existence of God - Ottesen Søvik, Atle (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2018)
Cosmological arguments for the existence of God defend God as a necessary being against (among others) the alternative that the universe came from nothing. “Nothing” is an ambiguous term, but when clarified it can be argued that a strong sense of the term is self-contradictory and thus impossible. This article discusses the arguments Lorenz B. Puntel has put forth in favour of this conclusion. The arguments herein rely on Puntel’s understanding of theoretical frameworks in explanations, which is also discussed. This article finds that there are good arguments against the possibility of nothing in a strong sense of the term, ending by considering this argument’s relevance to cosmological arguments for the existence of God.